Teachers' Strategies in Implementing Joyful Learning to Increase Interest in Learning Islamic Religious Education (PAI) at Nursyamsiani Islamic Private Elementary School - Safran Safran; Dwi Meutia Hasni; Siti Halimah (Yayasan Rahmat Islamiyah, 2026)
The low student interest in learning Islamic Religious Education (PA) in private Islamic elementary schools underscores the urgent need for more effective and enjoyable learning strategies, considering that religious education plays a central role in shaping students' morals, spiritual character, and learning motivation. This quantitative study aims to analyze the effect of teacher strategies in implementing a fun learning model on increasing interest in learning PAI at Nursyamsiani Islamic Private Elementary School. The research design used a survey method with an explanatory approach and involved 120 students in grades IV-V, selected through a proportional stratified random sampling technique. The research instrument was a Likert scale questionnaire that had been tested for validity and reliability, and the data were analyzed using simple linear regression and a t-test. Islamic Religious Education (PA) at Nursyamsiani Islamic Private Elementary School is effective in creating a fun, meaningful, and student-centered learning experience. The strategies used include educational games, reflective activities, group collaboration, and creative media, which consistently increase student interest in learning across cognitive, affective, and behavioral domains. A positive and supportive learning environment also strengthens students' motivation, self-confidence, and active engagement in learning Islamic Religious Education (PA). The conclusion of this study confirms that enjoyable learning is a relevant, empirically grounded pedagogical approach to strengthen students' learning motivation, while making theoretical contributions to the development of active learning models in Islamic education and offering practical implications for teachers in designing more creative, interactive, and developmentally appropriate learning experiences for students.